(untitled) (Research, Society and Development, 2023)
This study aimed to know the epidemiological profile of leprosy cases from Chapadinha - MA. This is a descriptive epidemiological research, of a quantitative nature, which used data from the Municipal Health Department, contemplating the following variables for the research: number of leprosy cases notified between 2017 and 2022; mode of entry into the health system; age range; sex; color or race; schooling; clinical form; operational criterion and output mode. 136 cases of leprosy were reported, with a higher prevalence observed in 2017, and the prevalence rate of leprosy in the municipality is considered average, 2.11 cases per 10,000 inhabitants, using the year 2022 as a reference. health system, 121 cases were registered as new cases. With regard to age group, the highest prevalence is in individuals aged between 35-49 years, with 42 cases. In the distribution of cases by gender, male predominance with 88 cases. As for the color of the people notified, there was a predominance of brown people, 86 cases. Regarding schooling, the most affected class are people with incomplete primary education 60 cases. The most prevalent clinical form of the disease was borderline with 66 cases. Regarding the operational criterion, 121 cases were reported as multibacillary. Of the 136 reported cases, we detected that 108 of them were successful in their treatments and had no deaths from leprosy. Chapadinha has an efficient treatment methodology, as 79.41% of patients progressed to cure.